Comportamiento cualitativo de las soluciones de ecuaciones diferenciales sin la condición signum - Martínez Sánchez, Francisco Rafael; Ruiz Chaveco, Antonio Iván (Revista Integración, temas de matemáticas, 1999)
In this paper we study the behaviour of solutions of second order damped nonlinear differential equation, x’’+φ(t,x,x’) + a(t)g(x)k(x’)=0, without the signum condition: x g(x) > 0 for all x different 0. We establish sufficient conditions for the continuability in the future and boundedness of solutions of this equation. Our results generalize a number of existing results.